The Certification Program Evaluation for Students in Vocational Schools using The CSE UCLA Model - Priyanto, Sugeng; Sahara, Siti; Nugraha, Hari Din (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to get an overview of the evaluation results and various obstacles faced in the implementation of machining competency test certification in Vocational High Schools (VHS). The evaluation method of this program is a qualitative research approach that uses the analysis of Techniques for Sequence Preference with Ideal Solution Similarity (TOPSIS). This study uses the CSE-UCLA model in designing program evaluation, which consists of five evaluation components: system assessment, program planning, program implementation, program improvement, and certification. Data collection involved subjects who were researched by filling out questionnaires, including school principals, vice principals for curriculum, deputy principals for industrial relations, deputy principals for facilities and infrastructure, heads of machining programs, workshop heads, machining productive teachers, and competency certification institutions/professional certification institutions in schools. Participants involved in collecting information used survey forms in five Vocational High Schools (VHS) in the Province of the Special Capital Region of Jakarta. In this study, five subjects of State Vocational High Schools were selected The study resulted that the machining competency test certification program has a good level of effectiveness, with certain components assessed as sufficient. Considering the dimension of the system assessment program, the value program planning category needs to be maintained or improved. In the context of program implementation, program improvement, and program certification, efforts are needed to improve the criteria for the better. Therefore, the findings of this study can be considered for the improvement of sustainable certification programs.